Valorization of coir peat in green extraction of valuable metals from spent lithium-ion batteries. - Sadaf Fatima; Muhammad Kaleem Khosa; Awal Noor; Sadaf Qayyum (PLoS ONE)
This research investigates an eco-friendly hydrometallurgical process for extracting valuable metals such as Li, Co, Ni, and Mn from spent lithium-ion batteries using biodegradable mixed organic acids, supported by coir peat as a natural reductant. Optimal leaching conditions (slurry density: 20 g/L, temperature: 55 °C, time: 55 minutes, stirring speed: 460 rpm, acid concentration: 50:50 mM ascorbic acid/citric acid) achieved metal efficiencies up to 85%. Incorporation of coir peat further enhanced the leaching efficiencies 98% for Li, 84.6% for Co, 85.6% for Ni, and 79.8% for Mn. Kinetic modeling revealed a chemically controlled dissolution process, with apparent activation energies of 43 kJ/mol (Li), 68 kJ/mol (Co), 47.8 kJ/mol (Ni), and 46 kJ/mol (Mn). Characterization through SEM confirms the morphological changes from spherical to uneven particle surfaces, FT-IR and XRD confirms the structural transformation of of cathode material before and after leaching, and UV-Vis spectroscopy showed the Co-complexes, Mn-complexes, and Ni-complexes at peaks around 380nm, 425 nm to 450 nm respectively due to reduction of metal complexes. The finding highlights the potential of biodegradable reagent and agro-waste material in developing sustainable battery recycling methods.